The Use of The Instagram Account @madridistaindo_brebes To Share Information With The Real Madrid Brebes Fan Community - Saputra, Firmansyah; Nurfalah, Farida; Rohida, Leni (Interaction Communication Studies Journal, 2026)
Social media has transformed how sports fans interact, enabling virtual communities that foster strong emotional bonds with their favorite clubs. However, online fan communities face challenges in maintaining content consistency, increasing engagement, and reinforcing collective identity amid growing competition. This study examines how members of the Pena Real Madrid Brebes community use Instagram and explores their motives for following the @madridistaindo_brebes account. Using a descriptive qualitative approach, data were collected through interviews, observations, and literature review, then analyzed using the Miles and Huberman model. The findings reveal that Instagram serves as the community’s primary communication medium, with content distributed through features such as feeds, Stories, and Reels. These features are optimized to deliver information, entertainment, and interactive content. Members’ motivations align with the uses and gratification framework. Overall, Instagram plays a central role in fulfilling both informational and psychological needs while sthrengthening engagement within the fan community. Furthermore, this study contributes by providing empirical insight into how localized fan communities strategically utilize Instagram features to sustain engagement and reinforce collective identity, while extending the    application of uses and gratifications theory within the context of digital sports fandom.